1995
DOI: 10.1089/jop.1995.11.145
|View full text |Cite
|
Sign up to set email alerts
|

Topically Applied Hydralazine: Effects on Systemic Cardiovascular Parameters, Blood-Aqueous Barrier, and Aqueous Humor Dynamics in Normotensive Humans

Abstract: Local application of hydralazine has been found to alter intraocular pressure in animal eyes. This study was undertaken to determine, in normotensive humans, the effects of topically-applied hydralazine on systemic cardiovascular parameters, blood-aqueous barrier, and aqueous humor flow. Two different concentrations of hydralazine were used: 0.03%, and 0.1%. Twenty healthy normotensive subjects were studied. Blood pressure, pulse rate, and intraocular pressure were measured every hour for six hours after hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Some studies have shown that both topical and intraocular administration of NO donors reduced IOP [30][31][32], while others reported that topical NO donors increased the IOP without affecting aqueous humor formation [33] or outfl ow facility [34] . Yet, other studies have shown that NO donors have no effect on the IOP in rabbits [35] or humans [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that both topical and intraocular administration of NO donors reduced IOP [30][31][32], while others reported that topical NO donors increased the IOP without affecting aqueous humor formation [33] or outfl ow facility [34] . Yet, other studies have shown that NO donors have no effect on the IOP in rabbits [35] or humans [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors report that topical and intraocular NO donors decrease IOP (Nathanson and McKee, 1995;Behar-Cohen et al, 1996), possibly by increasing conventional out¯ow facility (Schuman, Erikson and Nathanson, 1994). By contrast, other studies ®nd that topical NO donors increase IOP without affecting aqueous production (Larson et al, 1995) or tonographic out¯ow facility (Krupin et al, 1977). Interestingly, there are also reports that systemic NOS inhibition has no effect on IOP in conscious humans (Kiss et al, 1999) and rabbits (Taniguchi et al, 1998).…”
Section: Introductionmentioning
confidence: 88%
“…Administration of NO donors or overexpression of NO producing enzyme endothelial nitric oxide synthase (eNOS) results in increased outflow facility and/or decreased IOP in a number of animals including humans (Dismuke et al, 2008; Heyne et al, 2013; Larsson et al, 1995; Nathanson, 1992; Stamer et al, 2011). Nitric oxide synthase has also been detected in the tissues of the outflow pathway (Nathanson and McKee, 1995) and inhibition of this enzyme results in decreased outflow (Schneemann et al, 2002).…”
Section: Introductionmentioning
confidence: 99%